Critical Pedagogy and Islamic Education: Curriculum Reconstruction towards Transformative Learning - Ruslan Ruslan; Luthfiyah Luthfiyah (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2026)
This study aims to analyze the relevance of critical pedagogy in Islamic education and to formulate a reconstruction of the Islamic Religious Education (IRE) curriculum towards transformative learning. This research uses a qualitative approach with the type of library research. Data sources in this study consist of primary and secondary data. Primary data consists of main works discussing critical pedagogy, Islamic education, and curriculum theory, while secondary data includes nationally and internationally reputable journal articles, as well as academic books relevant to the research topic. Data analysis techniques are carried out using content analysis, which is interpretive-critical in nature. The research results show that critical pedagogy has strong alignment with Islamic educational values, particularly in the aspects of reflection (tafakkur), dialogue, and self-transformation. The integration of critical pedagogy into the IRE curriculum can be carried out through dialogical, contextual, reflective, and transformative principles. The reconstruction of this curriculum not only changes the learning structure but also the education paradigm from knowledge transmission towards the formation of critical awareness and social action. The implication of this reconstruction is the realization of transformative learning that can develop critical thinking skills, social awareness, and the contextual internalization of Islamic values. This study provides theoretical contributions to the development of an Islamic education curriculum based on critical pedagogy as well as practical implications for strengthening the quality of IRE learning that is more relevant to the challenges of the times.